MNL-Network: A Multi-Scale Non-local Network for Epilepsy Detection From EEG Signals - Zhang, Guokai; Yang, Le; Li, Boyang; Lu, Yiwen; Liu, Qinyuan; Zhao, Wei; Ren, Tianhe; Zhou, Junsheng; Wang, Shui-Hua; Che, Wenliang (Frontiers in Neuroscience, 2020)
Epilepsy is a prevalent neurological disorder disease that threatens human health in the world. The most commonly used method to detect epilepsy is using the electroencephalogram (EEG). However, the epilepsy detection from the EEG is a time-consuming and error-prone work because of the different experience levels of physicians. To handle this challenge, in this paper, we propose a multi-scale non-local (MNL) network to achieve automatic EEG signal detection. Our MNL-Network is based on 1D convolution neural network involving two specific layers to improve the classification performance. One layer is named the signal pooling layer which incorporates three different sizes of 1D max-pooling layers to learn the multi-scale features from the EEG signal. The other one is called a multi-scale non-local layer, which calculates the correlation of different multi-scale extracted features and outputs the correlative encoded features to further enhance the classification performance. To evaluate the effectiveness of our model, we conduct experiments on the Bonn dataset. The experimental results demonstrate that our MNL-Network could achieve competitive results in the EEG classification task.